To Maintain an Independent Course. Inter-war Indonesian Nationalism and International Communism on a Dutch-European Stage. (2nd September 2015) - Stutje, Klaas
Abstract : Decolonization is an inextricable part of the history of the Cold War, and its history begins far before the end of the Second World War. Indonesian anti-colonialism manifested itself in the Netherlands already in the inter-war years. This article examines how Indonesian nationalist students in the Netherlands tried to set their own political agenda against established political forces of the state, political parties, and transnational organizations. As an answer to their isolated position in the Netherlands, they soon focused on the international terrain, and reached out to anti-colonial activists in other European countries. As such they got involved with prestigious international networks around the League against Imperialism, and encountered other political forces such as the Comintern. This article tries to answer the question of whether the students succeeded in maintaining their independent course or were implicated in international communism: a question that remained relevant for much of the post-colonial Cold War era.